Psychometric Analyses of the Multiple Intelligences Developmental Scales MIDAS-Kids. - Pizarro Sánchez, Raúl; Colarte Troncoso, Patricia; Machuca Silva, Luis; Donoso Zamora, Fernando; Martínez Castillo, María; Walker Casanova, Inés (Revista de Psicología, 2002)
This methodological research has been a key component of Crisol Dorado Projects, Quilpué City Hall Department of Education, Chile, 2002-2004. Data consisted of Shearer´s MIDAS-Kids Scales (1996-2002) administered to 1,070 7th graders, 15 different public schools, Quilpué, Chile, 2002. MIDAS-Kids Scales presented excellent psychometrics: Mean Difficulty = 0.5357; Mean Discrimination = 0.8043; and, Cronbach´s Alfa Reliability Coefficient = 0.9649. By using stepwise models and Total Score as criterion, 8 significant regressions were analyzed. They ranged from R = 0.874 (F = 3,465.211; p = 0.000) for Intrapersonal Multiple Intelligence (MI), to R = 1.000 (F = 6,82E+16; p = 0.000) for all 8 MIs. Kinesthetic, Logical-Mathematical and Intrapersonal MIs significantly favored boys. For testing Gardner´s Frames of Mind Theory (1983, 1994), a confirmative Factorial Analysis was computed: Intrapersonal and Interpersonal (Personal MIs) appeared under factor 1; and, Musical MI was equally distributed in factors 7 and 8.